Psychometric Analysis of the Factors Modeling Islamic Moderation among Malaysian University Students - Yaakub, Muhamadul Bakir; Othman, Khatijah; Nik Nazli, Nik Nadian Nisa (2018)
This study is investigating the psychometric properties of the five componential factors of Islamic Moderation Instrumentation (IMI) among students of Malaysian Higher Learning Institutions (MHLI). The five componential factors of IMI is a newly constructed instrument to measure the Islamic moderation theory within the practices of students within MHLI. The data for this study were collected by using the random sampling from six public universities in Klang Valley, Malaysia. The questionnaire was the primary tool for the data gathering. The data were analyzed using Structural Equation Modeling technique using AMOS 23 version software. The findings showed that the five componential factors of Islamic Moderation’s Instrumentation (IMI) are positively significant and correlated with each variable. The psychometric data suggest that the five factors modeling Islamic moderations are the cycle of IM-MHLI between balance and moderate.